Fetal not immune hydrops proposed a flowchart for the etiologic diagnosis - Quiroga de Michelena, María (2015)
OBJECTIVE: To propose a protocol for the systematic study of hydrops fetalis in order to obtain an etiologic diagnosis. SETTING: Genetics Specialized Medical Center, Lima, Peru. MATERIAL AND METHODS: The proposed fluxogram is based on the study of 27 cases of non-immune fetal hydrops referred for chromosome analysis during the past ten years. Cytogenetic results, the evolution of the pregnancies, ultrasonographic images and pathologic studies were reviewed. Chromosome analysis were performed in 25 cases: 18 in amniotic fluid, 9 in chorionic villi and 2 in blood of the newborn. RESULTS: Eleven 11 (44%) cases had chromosomal abnormalities: 6, Turner syndrome; 3, trisomy 21; 1, trisomy 13, and 1, trisomy 7. The pathology of the placenta suggested infection in 2 cases. In one of these, the karyotype was normal, male; in the other, the cell culture was unsuccessful. In other cases with normal chromosomes, the pathologic study of the fetus or stillborn showed congenital malformations that could explain the development of hydrops. In 33% of cases in our series, a cause could not be identified. CONCLUSIONS: High proportion of idiopathic cases may be at least partially due to the lack of standardized criteria and methodologies to ascertain the origin of the hydrops. The proposed protocol (fluxogram) should facilitate the etiologic diagnosis, thus allowing genetic counseling and prevention of recurrence.